Systematic Analysis of Expression and Prognostic Values of Lysyl Oxidase Family in Gastric Cancer - Wang, Li; Cao, Shan; Zhai, Rujun; Zhao, Yang; Song, Guodong (Frontiers in Genetics, 2022)
Background: Gastric cancer remains the fifth most commonly diagnosed malignancy worldwide, with a poor prognosis. The LOX family, a type of secreted copper-dependent amine oxidases, is comprised of five homologous members and has been reported to be dysregulated in a number of different type cancers. However, the diverse expression patterns and prognostic values of LOX family in gastric cancer have yet to be systematically analyzed. Methods: ONCOMINE, GEPIA, UALCAN, Kaplan–Meier Plotter, LOGpc, cBioPortal, GeneMANIA and Metascape databases were utilized in this study to analyze the expression, prognostic values, mutations and functional networks of LOX family in gastric cancer. Results: The mRNA expression levels of LOX, LOXL1 and LOXL2 were significantly higher in GC, the expression level of LOXL3 was contrary in different databases, while the expression level of LOXL4 made no difference; the expression levels of LOX, LOXL1 and LOXL3 were higher in stages 2-4 than that of normal tissues and stage 1, while the mRNA level of LOXL2 in stage 1–4 was higher than normal tissues; patients with high expression of LOX and LOXL 2-4 had poor OS; the genes correlated with LOXL2/4 were enriched in extracellular matrix organization, vasculature development and skeletal system development. Conclusion: Our results indicated that the LOX family, especially LOX and LOXL2, might play an important role in GC oncogenesis, and they may become biomarkers for predicting tumor prognosis and potential targets for tumor therapy.